The Effect Of Leadership, Organizational Behavior On Employee Performance, Work Discipline As Intervening Variable - Rejeki Bangun; Sri Langgeng Ratnasari; Mira Yona; Renny Waty (BENING, 2022)
Employee performance is an interesting topic in the field of human resource management to be researched. To achieve performance, the human resource factor is very dominant and influential. This research aims to determine the effect of leadership on work discipline, the influence of organizational behavior on work discipline, the effect of work discipline on employee performance, the influence of leadership on employee performance, the influence of organizational behavior on employee performance, the influence of leadership and organizational behavior on employee performance through work discipline. This research is quantitative research. The population is 123 employees of PT. TMI with a sample of 123 employees. The sampling technique uses census techniques. Data analysis techniques using multiple linear regression and path analysis. The results of this research are leadership has a significant effect on work discipline, organizational behavior has a significant effect on work discipline, work discipline has a significant effect on employee performance, leadership has a significant effect on employee performance, organizational behavior has a significant effect on employee performance, leadership insignificantly effect on employee performance through work discipline, organizational behavior insignificantly effects on employee performance through work discipline.